The Peculiarities of Students’ Subjective Social Well-being Puring the covid-19 Pandemic Depending on Their University Attendance Mode - Baranauskienė, Ingrida; Kovalenko, Alla; Hryshchuk, Eliso; Rohal, Nina (Social Welfare: Interdisciplinary Approach, 2022)
The study examined the peculiarities of the subjective social and psychological well-being of general civil and military students during the Covid-19 pandemic, depending on the applied attendance modes: distance or face-to-face. General civil students had higher sleep quality, but they had less social contacts, compared to military students. The integral indicator of subjective social well-being was average in general civil and military students, and the differences were determined only for “social approval” scale, whose value was significantly higher in general civil students. The heaviest barrier in interpersonal communication for general civil and military students was inadequate expression of emotions; and inflexibility and vagueness of emotions were the least pronounced. Factors important for general civil students’ psychological well-being were social approval, purposefulness in their aspirations and emotional matching. At the same time, three factors were determined for military students: perceived independence, social reassurance and emotional control during interactions.